(untitled) (Asian Journal of Social Science Studies, 2022)
At present, short videos are still the trend of the industry. The research of this paper will be based on the theoretical perspective of dramaturgy theory and use the typical research methods named case analysis and content analysis to analyze the popular video blogger „Zhihao will‟ on a specific short video platform Douyin, which is an another official version of Tiktok used in the mainland of China, to conduct analysis and research, and to find out how to establish personal brands basically in the short videos era. After selecting and doing a research on the video contents released by the research subjects from 2018 to 2022, it is found that in the process of using short video as a medium to transmit content, a certain label for characters in short videos are necessarily needed for spreading its desired aims and contents to leave the first impression on audiences.